ANALISIS PENGEMBANGAN WEBSITE www.cirebonkota.go.id DALAM PELAKSANAAN ELECTRONIC GOVERNMENT DI PEMERINTAH KOTA CIREBON - Vien Nazmi Fadhilah Putri; Budi Puspo Priyadi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The task of the Government is providing good service to the community. Efforts that can be made with respect to such matters, that is to optimize the utilization of information and communication technology. The utilization of information technology by Governments is called electronic government, or e-Government. The city is one of the cities of Cirebon in West Java province who are implementing e-Government. This research aims to know the development of the website in the implementation of eGovernment as well as the factors that influence the implementation of e-Government. This research is a descriptive qualitative study types with data collection process through interview, observation and documentation. The stages of the implementation of e-Government that are used as a factor that influence the implementation. Things that affect the implementation of e-Government that is, there is no maximum support where the government rules the management of e-Government. Capacity financial resources, human resources and information technology infrastructure are inadequate. The advice that can be given by researchers to improve the implementation of e-Government, is held in cooperation with stakeholders, the capacity of human resources by holding technical training in a periodic environment, the procurement network infrastructure that is more stable, the massive socialization to society about the existence of eGovernment and its use as well as improving the look of the website to make it more interesting and interactive.